2023
DOI: 10.1007/s00784-023-04969-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nystatin oral rinse on oral Candida species and Streptococcus mutans among healthy adults

Abstract: Objectives To examine the effect of Nystatin oral rinse on oral Candida species and Streptococcus mutans carriage. Materials and methods Twenty healthy adults with oral candidiasis participated in the single-arm clinical trial and received Nystatin oral rinse for 7 days, 4 applications/day, and 600,000 International Units/application. Demographic-socioeconomic-oral-medical conditions were obtained. Salivary and plaque Candida species and Streptococcus muta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The knowledge that C. albicans’ catalase protects S. mutans in close contact with H 2 O 2 stress highlights the importance of developing strategies that target the disassociation of these partners in grime for the successful prevention and treatment of dental caries. Recently, Aljaffari and colleagues showed that the use of nystatin, an antifungal rinse, reduced the burden of S. mutans in saliva and plaque in patients with thrush, suggesting that approaches limiting colonization by C. albicans might help in the prevention and management of caries ( 56 ). Thus, when crafting new strategies to effectively combat caries, a multipronged approach including molecules that disrupt the synergism between caries-associated microorganisms, prebiotics that favor antagonistic properties of health-associated microorganisms, and the introduction of beneficial commensals possessing distinct pathways that inhibit different cariogenic traits of caries-associated microorganisms should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge that C. albicans’ catalase protects S. mutans in close contact with H 2 O 2 stress highlights the importance of developing strategies that target the disassociation of these partners in grime for the successful prevention and treatment of dental caries. Recently, Aljaffari and colleagues showed that the use of nystatin, an antifungal rinse, reduced the burden of S. mutans in saliva and plaque in patients with thrush, suggesting that approaches limiting colonization by C. albicans might help in the prevention and management of caries ( 56 ). Thus, when crafting new strategies to effectively combat caries, a multipronged approach including molecules that disrupt the synergism between caries-associated microorganisms, prebiotics that favor antagonistic properties of health-associated microorganisms, and the introduction of beneficial commensals possessing distinct pathways that inhibit different cariogenic traits of caries-associated microorganisms should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The trial procedure has been detailed previously [ 17 ]. Briefly, during the baseline visit, a questionnaire was used to collect data on the participants’ demographic and socioeconomic background, and oral hygiene practice.…”
Section: Methodsmentioning
confidence: 99%
“…that could not be identified via colony morphology [ 9 ]. Salivary cytokine/chemokine at three time points (baseline, 1 week and 3 months after Nystatin rinse) was assessed in the University of Rochester Human Immunology Center Core Lab facility, detailed previously [ 17 ]. Immune marker data from the trial were used for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, nystatin-treated biofilms exhibit distinctive halo-shaped microcolonies, and there is a downregulation in the core EPS coverage and expression of the gtfD and atpD genes of S. mutans [ 45 ]. Furthermore, investigations into the use of nystatin oral rinse have indicated its impact on oral carriage of C. albicans and S. mutans , suggesting that oral antifungal treatments may effectively influence S. mutans salivary carriage [ 73 ]. These findings point to antifungal treatments as a growing potential strategy for managing cariogenic microorganisms in oral environment.…”
Section: The Influence Of External Factors On Oral Microbiomesmentioning
confidence: 99%